Zai Technology and Integrated Nutrient Management for Improved Soil Fertility and Increased Sorghum Yields in Kitui County, Kenya - Kebenei, Mercy Cheruto; Mucheru-Muna, Monicah; Muriu-Ng'ang'a, Felista; Ndung'u, Charles Kimani (Frontiers in Sustainable Food Systems, 2021)
Deteriorating soil fertility, low unreliable rainfall and soil moisture stress has resulted to low crop yields among farmers of sub-Saharan Africa (SSA), necessitating a search for more sustainable production practices. Zai technology has the ability to promote soil moisture retention and enhances soil fertility. A four-seasons field experiment was conducted to assess the impact of Zai technology combined with cattle manure and inorganic fertilizer on selected soil properties and sorghum yields in Kabati, Kitui County. The experiment was set up in a Randomized Complete Block Design (RCBD) with eight treatments replicated thrice with sorghum Gadam as the test crop. Soil sampling was done at the beginning of the first season and at the end of the fourth season at a dept of 0-15 cm across each plot for laboratory analyses. From the results, soil pH significantly (p<0.05) increased in all the treatments with manure application either solely or in combination with mineral fertilizer. The increase in electrical conductivity was significant at p<0.05 in all the treatments after four cropping seasons. Total organic carbon significantly increased in Zai with cattle manure (p= 0.045), conventional with no input (p= 0.038) and conventional with cattle manure (p= 0.045). Available phosphorous significantly (p<0.05) increased in Zai with cattle manure (p= 0.022), Zai with full recommended mineral fertilizer rate (p= 0.013), Zai with cattle manure and half rate mineral fertilizer (p= 0.021) and conventional with cattle manure and half rate mineral fertilizer (p= 0.039) while total nitrogen significantly (p<0.05) reduced after the four cropping seasons. Zai treatments had a significant (p=0.05) positive effect on grain yield in SR18 and SR19 seasons and on stover yield in SR18, LR19 and SR19 seasons. Zai with cattle manure and half rate mineral fertilizer recorded 28% and 33% higher grain yield than their conventional counterparts. This study concluded that positive impacts on important soil properties and crop yield could be realized when Zai technology is utilized in combination with either sole manure or manure combined with mineral fertilizer and this could be used as a strategy to improve crop production in eastern Kenya and other arid and semi-arid areas.